2020
DOI: 10.1111/mmi.14462
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term kinetics of rRNA degradation in Escherichia coli upon starvation for carbon, amino acid or phosphate

Abstract: Ribosomes are absolutely essential for growth but are, moreover, energetically costly to produce. Therefore, it is important to adjust the cellular ribosome levels according to the environmental conditions in order to obtain the highest possible growth rate while avoiding energy wastage on excess ribosome biosynthesis. Here we show, by three different methods, that the ribosomal RNA content of Escherichia coli is downregulated within minutes of the removal of an essential nutrient from the growth medium, or af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 66 publications
(89 reference statements)
9
36
0
Order By: Relevance
“…The methodology allowed us to quantify the changes in total rRNA and total mRNA per OD unit of bacterial culture over the first 80 min of starvation for isoleucine. In accordance with other reports (Ben-Hamida and Schlessinger, 1966;Jacobson and Gillespie, 1968;Maruyama and Mizuno, 1970;Zundel et al, 2009;Piir et al, 2011;Fessler et al, 2020), we find that the stability of rRNA is compromised upon nutrient starvation, resulting in a drop in rRNA per OD unit to 70% of the pre-starvation level within the first 80 min of an amino acid starvation. Because rRNA constitutes the vast majority of cellular RNA, this drop affects the quantification of all other RNA species in the cell if the RNAseq data is normalized solely to the sequencing depth of the samples in the conventional way (referred to here as RPKM-normalization, Figure 6).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The methodology allowed us to quantify the changes in total rRNA and total mRNA per OD unit of bacterial culture over the first 80 min of starvation for isoleucine. In accordance with other reports (Ben-Hamida and Schlessinger, 1966;Jacobson and Gillespie, 1968;Maruyama and Mizuno, 1970;Zundel et al, 2009;Piir et al, 2011;Fessler et al, 2020), we find that the stability of rRNA is compromised upon nutrient starvation, resulting in a drop in rRNA per OD unit to 70% of the pre-starvation level within the first 80 min of an amino acid starvation. Because rRNA constitutes the vast majority of cellular RNA, this drop affects the quantification of all other RNA species in the cell if the RNAseq data is normalized solely to the sequencing depth of the samples in the conventional way (referred to here as RPKM-normalization, Figure 6).…”
Section: Discussionsupporting
confidence: 93%
“…As seen in Supplementary Figure S1A, the ratio of plasmid reads to total reads of the three replicates taken during steady-state growth varied only by~1%, indicating a high reproducibility of the data. In contrast, as starvation progressed within the 80-min time series, the ratio of plasmid reads/total reads increased, indicative of a decline in total RNA levels from the experimental samples, which is consistent with the net negative effect of ppGpp on the activity of RNA polymerase (Fiil et al, 1972;Sarubbi et al, 1988) and breakdown of rRNA (Zundel et al, 2009;Fessler et al, 2020) and tRNA (Svenningsen et al, 2017) upon starvation. However, the correlation deviated from the expected ratio at the 20-min time point with approximately 30% from the trend.…”
Section: Overview Of Spike-in Methodology and Rnaseq Datasupporting
confidence: 67%
See 1 more Smart Citation
“…Unstable rRNA has been also reported, using a similar normalization method than with tRNA studies. Fessler et al (2020) looked at the kinetics of different filter-resuspend starvation regimens, showing that while glucose starvation produces minimal instability of rRNA, isoleucine and phosphate starvation reduced ribosome content in a similar manner than previosly observed by tRNA ( Svenningsen et al, 2016 ). Again, the authors concluded that although (p)ppGpp may contribute, it is not essential for the degradation of rRNA, instead, inactive ribosomes are vulnerable to degradation.…”
Section: Effects Of Basal Levels Of (P)ppgpp In Escherichiamentioning
confidence: 99%
“…While changes in OD provide a clear measure of the growth of bacterial cultures in the steady state, where all cell constituents grow with the same rate, changes in optical density are complex to interpret upon disruption of the steady state, e.g. by starvation (Fessler et al 2020, Koch 1970. Accordingly, the correlation between OD measurements and bacterial concentration (CFU/ml) was good for exponentially growing cultures, but poor for the starved cultures ( Supplementary Fig.S1) .…”
Section: Northern Blots and Rrna Quantificationmentioning
confidence: 99%